On invariants of polynomial functions, II - Fukuma, Y. (Algebra and Discrete Mathematics, 2021)
Let P be a finite partially ordered set. In our previous paper, we defined the sectional geometric genus gᵢ(P) of P and studied gᵢ(P). In this paper, by using this sectional geometric genus of P, we will give a criterion about the case in which P has no order.